Jeremiah 32: A Hinge between Restoration and Disaster - de Waard, Henk (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2023)
Jeremiah 32 exhibits a complex combination of the contrasting motifs of disaster and restoration. The present article argues that these twofold contents of the chapter reflect its original literary function as a hinge between the Book of Consolation (Jer 30–31) and the stories about Judah’s collapse (Jer 34–45). Due to later developments, Jer 32 lost its original hinge function, as the chapter was integrated into the expanded Book of Consolation (Jer 30–33).